Affective-sexual relationships and eating disorders in obesity context - a systematic review - Veiga-Branco, Augusta (2015)
In human intimacy, affective-sexuality (Ambler, 2012) is variable which promotes physical and emotional well-being in intimate relationships, in general (Brigitta, 2004), and in obese, in particular. Apart from obesity as a risk factor for chronic diseases there is clear correlation between obesity and negative emotional states and vice versa (Kadioglu, 2009; Larsen, 2007). Some studies present a correlation between these two variables, showing body image and self-perceptionas two variables in sexual experience, particularly in female (Alba, 2013, Arcelus, 2012). This study aims at assessing the connection between affective-sexual relationships and eating disorders in overweight context from a sample of articles on this topic. according to the methodology PICO, it was conducted a research on electronic databases Pubmed and B-On, between June 9thand July 9th, 2014, with retrospection studies until January 2004. Keywords such as Sexuality, Obesity and Intimate Relationship were used as research strategies, in order to extract abstract and select studies. 74 studies were found and 10 were selected for final analysis. Studies present some controversies about those variables statistical relationships. Only 7 in 10 studies - samples from Italy, New Zeeland, Portugal, Canada and Iron- provide evidence of statistically significant associations between sexuality and obesity and 3 studies in 10 studies - with samples from Turkey and Romanyrefute previous data. It was found a reduced number of studies about the connection between sexuality and obesity. However, their results allow us to affirm that overweight and high body mass index (BMI) show adverse effects on sexuality in obese patients.